Predictability in Spatially Extended Systems with Model Uncertainty. II - Duan, J. (Электронное моделирование, 2009)
Macroscopic models for spatially extended systems under random influences are often described by stochastic partial differential equations. Some techniques for understanding solutions of such equations, such as estimating correlations, Liapunov exponents and impact of noises, are discussed. They are relevant for understanding predictability in spatially extended systems with model uncertainty, for example, in physics, geophysics and biological sciences. The presentation is for a wide audience. Рассмотрены некоторые методы представления решений стохастических дифференциальных уравнений в частных производных, в частности в задачах корреляции оценки, экспоненты Ляпунова и воздействие шумов. Методы пригодны для понимания предсказуемости в пространственно распределенных системах с неопределенностью модели, например, в физике, геофизике и биологических науках. Розглянуто деякі методи представлення розв'язків стохастичних диференціальних рівнянь у частинних похідних, зокрема у задачах кореляції оцінки, експоненти Ляпунова та впливу шумів. Методи придатні для розуміння передбачуваності у просторово розподілених системах з невизначеністю моделі, наприклад, у фізиці, геофізиці та біологічних науках.